Development of ionic conductive cellulose mat by solution blow spinning and laser-induced graphene from pineapple nanocellulose for use in flexible electronic devices - Claro, Pedro Ivo Cunha (2021)
In the face of environmental issues and aiming at electronic devices of rapid production at low cost, this doctoral thesis proposed two new and innovative approaches to obtain substrates, dielectrics, and electrodes from a single biopolymer: cellulose. In a first moment, a simple approach to produce low-cost flexible ionic conductive cellulose mats (ICCMs) using solution blow spinning (SB-Spinning) is reported. The electrochemical properties of the ICCMs were adjusted through infiltration with alkali hydroxides (LiOH, NaOH, or KOH), which enabled of ICCMs application as dielectric and substrate in oxidebased field effect transistors (FETs) and pencil-drawn resistor-loaded inverters. The FETs showed good electrical performance under operating voltage <2.5 V, which was strictly associated with the type of alkali ion incorporated, presenting satisfactory performance for the ICCM infiltrated with K+ ion. The inverters with K+ ions also presented good dynamic performance, with a gain close to 2. Regarding the cellulose-based electrodes, a second innovative approach is reported to synthetize laser-induced graphene (LIG) structures from carboxymethyl cellulose (CMC)-based ink containing LIG obtained from cellulose nanocrystals (CNCs) extracted from pineapple leaf fibers (PALFs). To prove this concept, zinc oxide ultraviolet (ZnO UV) sensors were designed varying the amount of LIG from CNCs. Sensor obtained from LIG written directly on paper substrate were also performed. The ZnO UV sensors designed with CMC-based ink showed responsivity 40-fold higher than that of paper directwritten LIG, as well as excellent electrical performance under flexion. These findings may open new promising possibilities for low-consumption wearable electronics, allowing the use of concepts such as the "Internet of Things" and opening the possibility of generating 100% organic cellulose-produced electronic devices.